2013
DOI: 10.1124/jpet.113.210724
|View full text |Cite
|
Sign up to set email alerts
|

DW09849, a Selective Phosphatidylinositol 3-Kinase (PI3K) Inhibitor, Prevents PI3K Signaling and Preferentially Inhibits Proliferation of Cells Containing the Oncogenic Mutation p110α (H1047R)

Abstract: Phosphatidylinositol 3-kinase, a isoform (PI3Ka) plays essential roles in cell metabolism, growth, and proliferation and has been validated as a promising anticancer target. In an effort to search for new PI3Ka-selective inhibitors, DW series compounds were designed and synthesized aiming to reduce the off-target effects of their parent compound PIK-75 [2-methyl-5-nitro-1-benzenesulfonic acid 2-[(6-bromoimidazo[1,2-a]pyridin-3-yl)methylene]-1-methylhydrazide], which was reported to selectively target PI3Ka. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…The PI3Kα inhibitor treatment results in G 1 phase arrest without killing cells in vitro [7] , which is consistent with lack of tumor regression in clinical settings. Sporadic studies have indicated the induction of apoptosis by NVP-BYL719, but this effect appears to be dependent on cell types [8] .…”
Section: Pi3kα-selective Inhibitorssupporting
confidence: 70%
“…The PI3Kα inhibitor treatment results in G 1 phase arrest without killing cells in vitro [7] , which is consistent with lack of tumor regression in clinical settings. Sporadic studies have indicated the induction of apoptosis by NVP-BYL719, but this effect appears to be dependent on cell types [8] .…”
Section: Pi3kα-selective Inhibitorssupporting
confidence: 70%
“…Recombinant protein was extracted by affinity purification. The PI3K kinase activity was determined in the increasing concentration of ATP and X-370 with PI3-Kinase HTRF™ Assay kit (Millipore) as described previously [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…Encouragingly, an in silico docking and MD simulation study of 33 PI3K inhibitors binding to conformations of the wild-type and mutant PI3Kα has demonstrated the conformation differences between an H1047 mutation and wild-type p110α for mutant-PI3Kα-specific drug design [161]. Other studies using structure-based drug design led to the development of mutated-PI3Kα targeted inhibitors, such as CH5132799 and DW09849 [162,163]. The drug efficacy of such new-generation inhibitors is in the process of characterization.…”
Section: Molecular Dynamics Simulation Inspires a New Generation Omentioning
confidence: 99%